Understanding waste management towards industry 4.0 / Nur Qistina Ahmad Faisal and Lizawati Abdullah - Ahmad Faisal, Nur Qistina; Abdullah, Lizawati (2021)
Sustainability and industry 4.0 are closely related. Industrial revolution 4.0 can enhance and achieve sustainable development. Waste management is part of sustainable development. Thus, recycling and making source separation is important although it is not commonly practice by most developed countries Are Malaysian ready for industrial revolution 4.0 in waste management technologies? This research aims to study Malaysian households' understanding on recycling benefits. Further, to examine their perception towards the 3r's concept. This concept has become popular back in the 1990s to represents Reduce, Reuse and Recycle. The concept of reduce is by reducing raw material that will be modified and manufactured as packaging, plastic bags, and others. While the concept of reuse is the repeated use of materials or goods without throwing them while the material is still in good shape and safe to be used. Besides that, the concept of recycle is when waste can be turned into new products without having to dispose ii. To achieve the objectives, this research adopts an online survey. The surveys were distributed via social media. The main findings showed that the respondents have the knowledge, awareness on the 3r's concept as well as the benefits. It is expected that the results can help the government, municipal council, and households to have an advance solution to improve the recycling program which will lead to efficient solid waste management towards industry 4.0.